1997
DOI: 10.1073/pnas.94.18.9705
|View full text |Cite
|
Sign up to set email alerts
|

Compromised mitochondrial function leads to increased cytosolic calcium and to activation of MAP kinases

Abstract: We have investigated in rat pheochromacytoma PC12 cells the activation of the mitogen-activated protein kinases ERK1 and ERK2 by the mitochondrial uncoupler carbonyl cyanide p-(trif luoromethoxy)phenylhydrazone (FCCP). This treatment slowly decreases ATP levels to 30% of control, whereas the internal calcium level rises very rapidly to 250% of control, derived from internal stores. Tyrosine phosphorylation of ERK1 and ERK2 increases gradually, starting after 5 min of treatment, to reach a maximum at 30 min; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 39 publications
5
71
0
Order By: Relevance
“…The activation of MAP kinase in A549, but not in C2C12 cells, probably reflects cell-specific differences in mitochondrial stress-induced activation of different signal pathways. Our results are consistent with a previous study (Luo et al, 1997), which showed that ERK1 and ERK2 were induced in phechromocytoma PC12 cells treated with FCCP, a mitochondria-specific ionophore, which also caused an increase in steady state [Ca 2+ ]. Additionally, increased mitochondrial H 2 O 2 , possibly representing mitochondrial stress, also induced MAP kinases in Hela cells (Nemoto et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
“…The activation of MAP kinase in A549, but not in C2C12 cells, probably reflects cell-specific differences in mitochondrial stress-induced activation of different signal pathways. Our results are consistent with a previous study (Luo et al, 1997), which showed that ERK1 and ERK2 were induced in phechromocytoma PC12 cells treated with FCCP, a mitochondria-specific ionophore, which also caused an increase in steady state [Ca 2+ ]. Additionally, increased mitochondrial H 2 O 2 , possibly representing mitochondrial stress, also induced MAP kinases in Hela cells (Nemoto et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
“…Uncoupling by FCCP reduced ATP by 30 -35% (Fig. 5B), which is in agreement with previous report (42). Subsequent increases in O 2 consumption by e K ϩ had no effect on the ATP level.…”
Section: Transient Increase In Oxygen Consumption In D Pc12 Cells Uposupporting
confidence: 82%
“…Other changes of AD could very well be linked to mitochondria because blockage of mitochondrial energy production shifts amyloid ␤-protein precursor metabolism to the production of more amyloidgenic forms of amyloid-␤ (Gabuzda et al, 1994), induces the production of A68 antigen (Blass et al, 1990), and activates the mitogen-activated protein kinase pathway (Luo et al, 1997;Perry et al, 1999;Zhu et al, 2000Zhu et al, , 2001, all features of AD.…”
Section: Discussionmentioning
confidence: 99%